Ways of euphemizing Russian profanity in the communicative space of the Internet - M. S. Dobrova (Шаги, 2025)
The modern Russian communicative situation is influenced by several trends, including jargonization and democratization of norms, which have influenced, among other things, a degree of loosening the taboo on obscene and profane in speech. One of the striking and unique phenomena of modern communication is virtual communication. Virtual communication, characterized by expressiveness and anonymity, manifests considerable popularity of the use of profanity and obscene expressions: these, due to the written nature of their embodiment, require new ways of veiling their unprintable form. Because of this, paragraphemic, phonographic and errative methods of euphemizing obscenities are beginning to be used in online communication. The article considers such new ways of euphemizing Russian obscene vocabulary in the communicative space of the Internet. The material for the article came from contexts obtained by the method of continuous sampling from texts of Internet communication: posts and comments on forums, Live Journal, social networks, and others. Our analysis demonstrates not only the variety of ways of paragraphemic and phonographic euphemization of the obscene on the Web, but also the creativity and adaptability of language phenomena to the needs of society, as well as the close connection between the expressiveness of obscene vocabulary and the discursive features of the Internet itself.